2019
DOI: 10.1186/s13027-019-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hepatitis B virus DNA replication level and anti-HBV therapy on microvascular invasion of hepatocellular carcinoma

Abstract: BackgroundChronic hepatitis B virus (HBV) infection is a major risk factor for the occurrence and development of cirrhosis and hepatocellular carcinoma (HCC). Microvascular invasion (MVI) of HCC is closely related to postoperative recurrence. We aimed to investigate the effect of HBV DNA replication levels and anti-HBV treatment on the occurrence of MVI in HCC.MethodsA retrospective analysis of the clinical and pathological data of 660 patients undergoing hepatectomy for hepatocellular carcinoma at the Affilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Importantly, a lower incidence of MVI has been found in AVT patients than that in non‐AVT patients (38.7% vs. 48.6%, p = 0.001), and AVT has been demonstrated as a protective factor of MVI (OR = 0.758) and early tumour recurrence (OR = 0.732). The other two studies further showed the similar conclusions that HBV replication was an independent risk of vascular invasion and AVT had an inhibitory effect on vascular invasion formation 43,44 . In addition, in a retrospective study that included 486 patients, we reported that the serum HBV levels might be associated with the extent of vascular invasion, and AVT could suppress the development of vascular invasion in patients with HBV‐related HCC 45 …”
Section: Hbv Infection and Pvttsupporting
confidence: 63%
“…Importantly, a lower incidence of MVI has been found in AVT patients than that in non‐AVT patients (38.7% vs. 48.6%, p = 0.001), and AVT has been demonstrated as a protective factor of MVI (OR = 0.758) and early tumour recurrence (OR = 0.732). The other two studies further showed the similar conclusions that HBV replication was an independent risk of vascular invasion and AVT had an inhibitory effect on vascular invasion formation 43,44 . In addition, in a retrospective study that included 486 patients, we reported that the serum HBV levels might be associated with the extent of vascular invasion, and AVT could suppress the development of vascular invasion in patients with HBV‐related HCC 45 …”
Section: Hbv Infection and Pvttsupporting
confidence: 63%
“…The molecular biological mechanisms of such a distinct influence remain to be clarified. Interestingly, given the previous studies which would suggest otherwise ( 16 , 32 ), we were surprised that preoperative HBV-DNA level was not found to be significantly associated with MVI in our HCC patients.…”
Section: Discussionmentioning
confidence: 52%
“…Twenty-one studies were screened in the full text evaluation, and according to our inclusion criteria, 15 irrelevant records were excluded. Finally, six studies met our inclusion criteria and were, therefore, included in this meta-analysis (Huang et al, 2017;Lei et al, 2016;Li et al, 2018b;Liu et al, 2019;Qu et al, 2019;Wei et al, 2017).…”
Section: Literature Searchmentioning
confidence: 99%
“…Included studies were published from 2016 to 2019, and Table 1 details characteristics of all included studies. One study had a prospective design (Lei et al, 2016), and all others had a retrospective design (Huang et al, 2017;Li et al, 2018b;Liu et al, 2019;Qu et al, 2019;Wei et al, 2017). In total, of 4,988 participants, ranging from 349 to 2,362, 1,005 participants had antiviral treatment, and 2,069 participants showed MVI.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%